Hasil Belajar Matematika pada Pembelajaran Kooperatif Two Stay Two Stray (Universitas Muhammadiyah Palembang, 2023)
Problems faced about the low student learning outcomes in algebraic form material. The reason for the low student learning outcomes is the lack of optimal action and learning models used in the learning process, thus making students make a lot of concept errors in algebraic form material. To be able to overcome the problem of learning outcomes, it is necessary to do cooperative learning type Two Stay Two Stray. The research method uses a True Experimental Design research design in the form of a Posttest Only Control Design. From the calculation of learning outcomes obtained by class VIIA by using Two Stay Two Stray cooperative learning obtained an average of and a standard deviation of , while class VIIC without using Two Stay Two Stray cooperative learning obtained an average of with the standard deviation . Based on the hypothesis test obtained and with and a significant level ? = 0.05. Because means that Ha is accepted. From testing Ha's hypothesis which states that